Antiferromagnetism in two-dimensional polyradical nanosheets. Issue 46 (5th November 2018) - Yang, Yang; Liu, Caixing; Xu, Xueli; Meng, Zhi; Tong, Wei; Ma, Zongwei; Zhou, Chun; Sun, Yuping; Sheng, Zhigao
Abstract : 2D polyradical nanosheets were prepared using interfacial polymerization and exhibited obvious antiferromagnetic behavior. Abstract : Two-dimensional (2D) organic magnetic materials have great value for research and applications in spintronics. However, unlike the diverse inorganic materials, finding 2D organic magnetic materials is still a major challenge. In this work, freestanding 2D organic magnetic polyradical (OMP) nanosheets were successfully synthesized using the polymerization of tris(2, 3, 5, 6-tetrachloro-4-ethynylphenyl)methyl radicals at a liquid/liquid interface. The OMP obtained has a 2D sheet-like morphology and possesses triarylmethyl radicals after polymerization, which can act as spin centers. With the magnetic exchange coupling between radicals, the OMP shows an antiferromagnetic behavior with a Néel temperature of 42.5 K. Besides the OMP, this discovery also provides a route for synthesis of other potential antiferromagnetic 2D organic materials, which can act as essential building blocks in 2D organic spintronic devices.